The usage of different fertilizer type in same soil character ization improvements in Tikrit - Halla Arshad Ali (Tikrit Journal of Pure Science, 2023)
This study included the effected of using different types of organic fertilizer in some soil chemical characterization productivity of okra plant. The experiment were designed  according (R.C.B.D),  with three replicates by using fertilizers remnants of cows and poultry, sludge were used. Three levels(10,20,40) ton/hectare were  used in comparison with different levels of mineral fertilizer (150+115+115), (230+230+300), (460+460+600) Kg/hectare .This treatment resulted in reduction of soil organic materials, which approached 2.53% as compared with organic fertilizers and increased, phosphorus and potassium levels. While the sludge treatment  increased organic material ,phosphorus and potassium  over 40 ton/hectare, as well as in an increase in the plant chlorophil contents. This increase was approximately 3.52mg/g. In overall comparison between the various fertilizers, the sludge produced equal effect with the different mineral fertilizers levels.